Reorienting the epistemology of research in Islamic studies: Critiquing the dominance of modern methodology through the Islamic scholarly manhaj - Vina Rahayu Chairunnisa; Khaerudin (Mishkat: Journal of Theology and Civilization, 2026)
The dominance of modern research methodology in Islamic studies has improved academic research quality but tends to position research methods as the starting point of inquiry, leaving the epistemological foundation rooted in the Islamic scholarly manhaj insufficiently addressed. This study aims to examine the dominance of modern research methodology in Islamic studies and formulate an epistemological reorientation from the perspective of the Islamic scholarly manhaj. A qualitative conceptual research design was employed using document analysis, conceptual analysis, comparative analysis, and conceptual synthesis of literature on Islamic epistemology and modern philosophy of science. The findings indicate that the primary challenge in Islamic studies lies not in the choice of research methods but in the epistemological paradigm underlying their application. This study proposes a conceptual framework that positions the Islamic scholarly manhaj as the foundation for selecting research methods through the integration of the Islamic Worldview, Islamic sources of knowledge, epistemological structure, and the Integration–Interconnection paradigm, thereby contributing to the development of a more integrative and contextually grounded research methodology for Islamic studies. Abstrak Dominasi metodologi penelitian modern dalam studi Islam telah meningkatkan kualitas akademik penelitian, tetapi cenderung menempatkan metode penelitian sebagai titik awal proses ilmiah sehingga fondasi epistemologis yang berakar pada manhaj keilmuan Islam belum memperoleh perhatian yang memadai. Penelitian ini bertujuan untuk menganalisis dominasi metodologi penelitian modern dalam studi Islam serta merumuskan reorientasi epistemologi melalui perspektif manhaj keilmuan Islam. Penelitian ini menggunakan pendekatan kualitatif dengan desain penelitian konseptual melalui studi dokumentasi serta analisis konseptual, komparatif, dan sintesis terhadap literatur mengenai epistemologi Islam dan filsafat ilmu modern. Hasil penelitian menunjukkan bahwa persoalan utama dalam studi Islam tidak terletak pada pemilihan metode penelitian, melainkan pada paradigma epistemologis yang melandasi penggunaannya. Penelitian ini menawarkan suatu kerangka konseptual yang menempatkan manhaj keilmuan Islam sebagai fondasi dalam menentukan metode penelitian melalui integrasi Islamic Worldview, sumber-sumber pengetahuan Islam, struktur epistemologi, dan paradigma Integration–Interconnection. Kerangka tersebut diharapkan dapat memperkaya pengembangan metodologi penelitian studi Islam yang lebih integratif, kontekstual, dan selaras dengan karakteristik epistemologi Islam.